3D metal freeform micromanufacturing. (August 2021) - Borasi, Luciano; Casamenti, Enrico; Charvet, Raphaël; Dénéréaz, Cyril; Pollonghini, Sacha; Deillon, Léa; Yang, Tao; Ebrahim, Fatmah; Mortensen, Andreas; Bellouard, Yves
Abstract: Despite remarkable progress made in recent years, producing freeform three-dimensional micro-components out of copper, silver or gold and their alloys remains an engineering challenge: current processes are either too slow to be economically viable, or produce porous or otherwise imperfect metal microstructures. Here we introduce an alternative, faster approach for the freeform fabrication of metal micro-components amenable to the processing of noble metals. The process begins with the 3D, micron-resolution, carving of arbitrarily shaped interconnected molds into amorphous silica using femtosecond laser micromachining and selective etching. This is followed by pressure infiltration of the mold with the molten metal, which is subsequently solidified. Metal architectures produced by this process have micron-scale resolution, are fully freeform and multiscale in geometry, and are made of dense metal, while the process speed largely exceeds what is achieved in current alternative metal microfabrication approaches. The resulting glass/metal combinations enable new micro-device architectures. Alternatively, by mold dissolution, self-standing micron-scale 3D metal parts are produced, of high metallurgical quality and with features sizes down to ~2 μm.